Adsorptive remediation of environmental pollutants using magnetic hybrid materials as platform adsorbents. (December 2021) - Ali, Nisar; Hassan Riead, MD Mahamudul; Bilal, Muhammad; Yang, Yong; Khan, Adnan; Ali, Farman; Karim, Shafiul; Zhou, Cao; Wenjie, Ye; Sher, Farooq; Iqbal, Hafiz M.N.
Abstract: Effective separation and remediation of environmentally hazardous pollutants are burning areas of research because of a constant increase in environmental pollution problems. An extensive number of emerging contaminants in the environmental matrices result in serious health consequences in animals, humans, and plants, even at trace levels. Therefore, it is of paramount significance to quantify these undesirable pollutants, even at a very low concentration, from the natural environment. Magnetic solid-phase extraction (MSPE) has recently achieved huge attention because of its strong magnetic domain and easy separation through an external magnetic field compared with simple solid-phase extraction. Therefore, MSPE appeared the most promising technique for removing and pre-concentration of emerging pollutants at trace level. Compared to the normal solid-phase extraction, MSPE as magnetic hybrid adsorbents offers the unique advantages of distinct nanomaterials and magnetic hybrid materials. It can exhibit efficient dispersion and rapid recycling when applying to a very complex matrix. This review highlights the possible environmental applications of magnetic hybrid nanoscale materials as effective MSPE sorbents to remediate a diverse range of environmentally toxic pollutants. We believe this study tends to evoke a variety of research thrust that may lead to novel remediation approaches in the forthcoming years. Graphical abstract: Image 1 Highlights: The persistence of environmentally related pollutants causes threats to the living ecosystems. Magnetic hybrid nanoscale materials as effective magnetic solid-phase extraction sorbents are discussed. An array of nano-adsorbents is given to remediate a diverse range of environmentally toxic pollutants.